HUBUNGAN ASUPAN CAIRAN, ASUPAN SERAT, DAN STATUS GIZI TERHADAP POLA DEFEKASI PADA ANAK SEKOLAH DASAR SDN 78 KOTA BENGKULU - Rahmadani, Qomariyah; Yuliantini, Emy; Sari, Ayu Pravita (Jurnal Gizi dan Pangan Soedirman, 2024)
Primary school children are an age group that is vulnerable to nutrition and health problems. One that is often faced by elementary school children is a shift in diet that tends to consume foods that are high in energy and low in fluid and low in fiber, which affects the defecation patterns experienced. This study aims to determine the relationship between fluid intake, fiber intake and nutritional status on defecation patterns of grade III primary school children at SDN 78 Bengkulu City. This study is quantitative with a cross-sectional design and used 62 respondent. The study was conducted from May-June 2024.. Data were collected through questionnaires and food recall forms for 3 x 24 hours. The results of univariate analysis obtained 58.1% of respondents with adequate fluid intake, 67.7% with insufficient fiber intake, 66.1% with normal nutritional status, 56.5% with irregular defecation patterns. The results of the chi square test showed no relationship between fluid intake (p=0.34) and fiber intake (p=0.90) to the pattern of decefation and there was a relationship between nutritional status (p=0.002) to the pattern of decefation. Based on this research, it is expected that respondents can maintain nutritional status and improve fluid and fiber intake.